Peranan Dinasti Abbasiyah Terhadap Peradaban Dunia - Iqbal, Iqbal (IAIN Palangka Raya, 2015)
Abbasiyah empire is which one empire in Islam. In History, Abbasiyah empire is top empire, so we called it as